A multifactorial score including autophagy for prognosis and care of COVID-19 patients. Issue 12 (1st December 2020) - Domdom, Marie-Angela; Brest, Patrick; Grosjean, Iris; Roméo, Barnabé; Landi, Maria Teresa; Gal, Jocelyn; Klionsky, Daniel J.; Hofman, Paul; Mograbi, Baharia
ABSTRACT: In less than eleven months, the world was brought to a halt by the COVID-19 outbreak. With hospitals becoming overwhelmed, one of the highest priorities concerned critical care triage to ration the scarce resources of intensive care units. Which patient should be treated first? Based on what clinical and biological criteria? A global joint effort rapidly led to sequencing the genomes of tens of thousands of COVID-19 patients to determine the patients' genetic signature that causes them to be at risk of suddenly developing severe disease. In this commentary, we would like to consider some points concerning the use of a multifactorial risk score for COVID-19 severity. This score includes macroautophagy (hereafter referred to as autophagy), a critical host process that controls all steps harnessed by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. Abbreviation list: ATG5: autophagy related 5; BECN1: beclin 1; COVID-19: coronavirus infectious disease-2019; EGR1: early growth response 1; ER: endoplasmic reticulum; DMVs: double-membrane vesicles; IBV: infectious bronchitis virus; MAP1LC3: microtubule associated protein 1 light chain 3; LC3-I: proteolytically processed, non-lipidated MAP1LC3; LC3-II: lipidated MAP1LC3; MEFs: mouse embryonic fibroblasts; MERS-CoV: Middle East respiratory syndrome-coronavirus; MHV: mouse hepatitis virus; NSP: non-structural protein; PEDV: porcine epidemic diarrhea virus; PLP2-TM: membrane-associated papain-like protease 2; SARS-CoV-2: severe acute respiratory syndrome coronavirus 2; TGEV: transmissible gastroenteritis virus.